Prospection of Remotely Piloted Aircraft (RPA) for Agriculture in Brazil - Severino, Elcio Manoel (2023)
In agriculture, the RPAs are used to perform various activities, such as spraying, agricultural mapping, surveillance, among others. The objective of this work was to conduct a quantitative research of patents related to the use of RPAs in agriculture in Brazil in the last 20 years, proposing to identify the main sectors of agribusiness that use the technology, future scenarios and trends of use. For this, a quantitative approach was adopted, of exploratory nature, by means of technological prospection having as database the Orbit and the INPI. As a result, 33 patents related to the theme were identified, of which 39.4% with guaranteed rights, 42.4% pending, 15.2% revoked and 3% in the public domain. It is concluded that the Brazilian agribusiness is increasingly using drones, UAV or RPA due to the various possibilities for use within the sector and the advantages arising from their use, such as reduced costs or better management practices.